Mitigate+ at COP28: Let’s talk about non-market approaches, youth in climate action, social equality in low-emission food system development and more! - CGIAR Initiative on Low-Emission Food Systems (2023)
Progress on implementing the work program on non-market approaches will comprise a topic that will take the spotlight at COP28 in Dubai. But what are non-market approaches? We will strive to answer that question in a session we are organizing at the Food and Agriculture Pavilion at COP28. The session takes place on 5 December 2023 from 18:30—19:30 UAE time.